2015
DOI: 10.1007/978-3-319-18609-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Analysing an Academic Field through the Lenses of Internet Science: Digital Humanities as a Virtual Community

Abstract: Abstract. Digital Humanities (DH) has been depicted as an innovative engine for humanities, as a challenge for Data Science, and as an area where libraries, archives and providers of e-research infrastructures join forces with research pioneers. However DH is defined, one thing is certain: DH is a new community which manifests and identifies itself via the Internet and social media. In this paper we propose to describe DH as a virtual community (VC), and discuss the implications of such an epistemic approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Nyhan and Duke-Williams (2014) analyzed Computers and the humanities (1966–2004) and Literary and Linguistic Computing (1986–2011), and found that a small group of people tend to co-author together, while the majority of authors do not connect with other co-authorship clusters. Salah et al (2015) explored nearly 700 DH-related journal articles from various sources, situating the community within a larger disciplinary context.…”
Section: Introductionmentioning
confidence: 99%
“…Nyhan and Duke-Williams (2014) analyzed Computers and the humanities (1966–2004) and Literary and Linguistic Computing (1986–2011), and found that a small group of people tend to co-author together, while the majority of authors do not connect with other co-authorship clusters. Salah et al (2015) explored nearly 700 DH-related journal articles from various sources, situating the community within a larger disciplinary context.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some scholars use not only academic social network platforms (such as ResearchGate, Academia. edu, or Mendeley) but also a variety of social media, such as Twitter, Facebook, Flickr, YouTube, Dropbox, blogs, and podcasts for scholarly communication [23]. These social media tools have expanded the possibilities of informal communication.…”
Section: Scholarly Communicationmentioning
confidence: 99%
“…Scholars rely on social media platforms (such as Twitter, Facebook, YouTube, blogs, and podcasts) for their communication, just like the rest of us. The use of these general purpose platforms is complemented by social network sites (SNS) tailored specifically for academic audiences (Salah et al, 2015). These socalled "academic social network sites" (ASNS) encompasses a variety of online platforms (such as ResearchGate and Academia.edu), but seek to bring the benefits of online networking to academia (Jordan, 2019).…”
Section: Introductionmentioning
confidence: 99%